The current state of the ERM implementation in Malaysia: An exploratory study - Kasim M.A.B.; Hanafi S.R.B.M.; Aziz A.A.; Kasim I.B. (Nova Science Publishers, Inc., 2023)
This paper reports the results of an exploratory study conducted to determine the stage and nature of Enterprise Risk Management (ERM) implementation in Malaysia. The study involves the High Performance GLCs in Malaysia (G20). The results revealed various interesting insights on the current state of the ERM in Malaysia.The overall results reported that most organizations were in the second or third year of ERM implementation; while a considerable portion of organizations were currently in the fifth year of implementing ERM. The existence of the CRO was also found to influence the degree of the ERM implementation. 2012 by Nova Science Publishers, Inc. All rights reserved.